Central bank communication in the financial crisis: Evidence from a survey of financial market participants - Bernd Hayo; Matthias Neuenkirch (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
In this paper, we study whether central bank communication has a positive effect on market participants' perception of central banks' (i) credibility, (ii) unorthodox measures, and (iii) independence. We utilise a survey of more than 500 financial market participants from around the world who answered questions in reference to the Bank of England (BoE), the Bank of Japan (BoJ), the European Central Bank (ECB), and the Federal Reserve (Fed). We find that market participants believe that the Fed communicates best, followed by the BoE, ECB, and BoJ. Similar rankings are found on the issues of credibility, satisfaction with unconventional monetary policy, and possible deterioration in independence. Using ordered probit models, we show that central bank communication has a positive effect on how central banks are perceived and understood, as it enhances credibility, increases satisfaction with unorthodox measures, and fosters perceived independence of central banks.
Keywords: E52; E58; 330; Central Bank; Communication; Credibility; Financial Crisis; Financial Market Participants; Independence; Survey; Unconventional Monetary Policy